Evaluación de la captura de carbono en las especies forestales Manilkara sp. “Quinilla” y Myrcia sp. “Rupiña”, en el centro de producción investigación Pabloyacu, Moyobamba - 2012 - Fuentes Cubas, Sandra (2013)
This paper attempts to quantify carbon sequestration in forest species Manilkara sp. "Quinilla" and Myrcia sp. "Rupina" in order to estimate the biomass and carbon (C) contained in the above mentioned species; This study was conducted at the Center for Production and Pabloyacu esearch, located in Marona village Moyobamba district, San Martin Department. The specific objectives were: Perform a biometric inventory of species Manilkara sp. "Quinilla" and Myrcia sp. "Rupina"; to determine the amount of carbon catch and biomass Manilkara sp. "Quinilla" and Myrcia sp. "Rupina"; to analyze and compare the amount of carbon sequestration between Manilkara sp. "Quinilla" and Myrcia sp. "Rupina"; related carbon capture and DAP of Manilkara sp. "Quinilla" and Myrcia sp. "Rupina". The problem was formulated: What is carbon sequestration in relation to the DAP, the species of Manilkara sp. "Quinilla" and Myrcia sp. "Rupina" in Pabloyacu Production Center and research? The variables proposed in the evaluation were the species Manilkara sp. "Quinilla" and Myrcia sp. "Rupina" as independent variable and carbon sequestration as a dependent variable. The hypothesis was: If we evaluate carbon sequestration in relation to DAP species of Manilkara sp. "Quinilla" and Myrcia sp. "Rupina" in Pabloyacu Research and Production Center, then the linear relationship between these variables to be direct. Applied research is descriptive and hypothesis testing used the correlation coefficient. The population was estimated at 1 having (10,000 m2) and the sample of 2,000 m2 divided into two sectors (1,000 m2 each). The activities included: the selection and description of the study area, the size of the sample and identifying areas of studies and the identification of the species, and to estimate biomass using the indirect method, using the following formula : BA = 2.53 and 0.1184 DAP to calculate the total carbon in plant biomass (t / ha), the following formula was used: CBV (t / ha) * 0.45 = BTV The carbon in the quantized area, one to the species Myrcia sp. was 8.15 t / ha, and the species Manilkara sp. record of 25.89 t / ha; in sector two, the species Manilkara sp. record of 26.21 t / ha, and the species Myrcia sp. record of 5.67 t / ha, the species Manilkara sp. "Quinilla" had the highest amount of carbon sequestration with average 26.05 tons / ha. Carbon is measured in the field of species Myrcia sp. was 8.15 t / ha, and the species Manilkara sp. recorded 25.89 t / ha; in sector two, species Manilkara sp. Recorded 26.21 t / ha, and the species Myrcia sp. recorded 5.67 t / ha, the species Manilkara sp. "Quinilla" had the highest amount of carbon sequestration with average 26.05 tons / ha; While the average of carbon captured by the species Myrcia sp. "Rupina" was 6.92 t / ha; on average, the carbon captured by both species was 16.48 t / ha. Comparing the DAP with the amount of carbon sequestration, these variables showed a direct relationship. Ie it was observed when the DAP increases the amount of carbon sequestered also increases, then we say that the linear regression between the two variables is straightforward.